Hybrid liposomes composed of amphiphilic chitosan and phospholipid: Preparation, stability and bioavailability as a carrier for curcumin. (20th January 2017) - Peng, Shengfeng; Zou, Liqiang; Liu, Weilin; Li, Ziling; Liu, Wei; Hu, Xiuting; Chen, Xing; Liu, Chengmei
Highlights: Hybrid liposomes composed of amphiphilic chitosan and phospholipid were prepared. The hybrid liposomes exhibited excellent ionic and thermal stability. Curcumin hybrid liposomes showed improved stability and sustained release. Bioavailability of curcumin was improved when loaded in hybrid liposomes. Abstract: Hybrid liposomes, composed of amphiphilic chitosan and phospholipid, were prepared and used to evaluate the effect of amphiphilic polymers on the properties of liposomes. Successful preparation of the hybrid liposomes was confirmed using physicochemical characteristics, including morphology, particle size and zeta potential. Physical stability studies (exposure to solutions of increasing ionic strength and heat treatment) indicated that the hybrid liposomes had better ionic stability than amphiphilic chitosan-based polymeric liposomes and higher thermal stability than traditional phospholipid liposomes. Curcumin was then encapsulated in the hybrid liposomes. Compared with phospholipid liposomes, the hybrid liposomes displayed better storage stability and more sustained curcumin release. Cellular uptake experiments showed that the hybrid liposomes significantly increased the bioavailability of curcumin. The study highlights the potential of well-designed stable hybrid liposomes that increase the stability and bioavailability of lipophilic bioactive, such as curcumin.